THE WORLD OF THE NURSE: “HERE WE NEVER REST”. CARE CONTEXT - Berrío, Gladys Guarín; Castrillón Agudelo, María Consuelo (Investigación y Educación en Enfermería, 2009)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Objective: to understand the context, goals and meanings that nurses give to their care roles. Methodology: qualitative investigation whose methodological approach was focused ethnography in nursing care to surgical patients in high complexity health institutes in Medellín, Colombia. The study is performed between 2005 and 2007. The data collection is done by means of participant observations and in-depth interviews to nurses. We carry out a total of 11 nurses’ interviews and observations of shifts changes, nursing rounds, medical rounds and patients discharge. We use an informed consent form that each interviewee signed. In open coded analysis we meticulously examin and compare searching, differences and similarities. Results: the findings make clear that nurses consider patient first of all as human beings and they believe that humanity is an essential component for those who you look after and is a value for those who provide care. Attention to every detail makes part of the nurse’s world in their care actions. They are responsible for everything in the service and it implies “having to have four eyes”. Conclusion: the nurses’ world, in the studied services, is characterized as a complex context that demands to be permanently attentive to multiple and simultaneous situations. In their own words is defined as “Here we never rest”.